From dioxime oxalates to dihydropyrroles and phenanthridines via iminyl radicals. - SCANLAN, EOIN (My University, 2008)
Dioxime oxalates are useful precursors for the clean generation of iminyl radicals by sensitised UV photolysis and can be adapted for serviceable preparations of 3,4-dihydro-2H-pyrroles and phenanthridines.
PUBLISHED
Keywords: Chemistry